2008
DOI: 10.1016/j.pain.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin inhibits the development and expression of neuropathic pain induced by paclitaxel in mice

Abstract: We evaluated the effect of low doses of systemically administered tetrodotoxin (TTX) on the development and expression of neuropathic pain induced by paclitaxel in mice. Treatment with paclitaxel (2mg/kg, i.p., once daily during 5 days) produced long-lasting (2-4 weeks) heat hyperalgesia (plantar test), mechanical allodynia (electronic Von Frey test) and cold allodynia (acetone drop method), with maximum effects observed on days 7, 10 and 10-14, respectively. Acute subcutaneous treatment with 1 or 3 microg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 50 publications
12
108
0
1
Order By: Relevance
“…These observations are consistent with those of other reports showing paclitaxel to induce mechanical allodynia in mice (4,19). The present study further demonstrated a significant attenuation of paclitaxel-induced mechanical allodynia by repeated milnacipran or fluvoxamine treatment.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These observations are consistent with those of other reports showing paclitaxel to induce mechanical allodynia in mice (4,19). The present study further demonstrated a significant attenuation of paclitaxel-induced mechanical allodynia by repeated milnacipran or fluvoxamine treatment.…”
Section: Discussionsupporting
confidence: 94%
“…to mice at doses of 0.5-2 mg/ kg, once per day for 5 consecutive days. Paclitaxel dosing was determined based on previous reports that used mice (4,19). Milnacipran hydrochloride or fluvoxamine maleate (Sigma Chemical Co., St. Louis, MO) was administered i.p.…”
mentioning
confidence: 99%
“…Capsaicin 0.025% cream, 8% patches or 5% lidocaine patches have all been shown to be efficacious in a variety of other peripheral neuropathies, 176,177 although robust evidence for their use in CIPN is lacking. A number of potential treatments are being evaluated, including topical menthol (an inactivator of nociceptor voltage-gated sodium channels), 178 tetrodotoxin (voltage-gated sodium channel inhibitor) 179 and the cannabinoid receptor agonists WIN55, 212-2 and AM1710. 180 …”
Section: Treatment Of Pain In Cancer Survivorsmentioning
confidence: 99%
“…Both voltage-and ligand-gated ion channels have been shown to play a role in chemotherapy-induced changes in nociceptive behaviors. Included in these are sodium channels, 137,234,235 calcium channels, 155,173,[236][237][238] ATP-gated channels, 239 acid-sensing channels, 239 and TRP channels, [240][241][242] although much controversy persists regarding which channels mediate different modalities of chemotherapy-induced behaviors. Gabapentin, which binds to the α 2 δ subunit of the calcium channel, 243 has been investigated in preclinical studies and found to have variable effects on nociceptive behaviors, depending on the class of chemotherapy administered.…”
Section: Ion Channel Modulationmentioning
confidence: 99%